Layer-by-Layer Coating of Single-Cell Lacticaseibacillus rhamnosus to Increase Viability Under Simulated Gastrointestinal Conditions and Use in Film Formation - Sbehat, Maram; Altamimi, Mohammad; Sabbah, Mohammad; Mauriello, Gianluigi (Frontiers in Microbiology, 2022)
Probiotics and prebiotics are widely used as functional food ingredients. Viability of probiotics in the food matrix and further in the digestive system is still a challenge for the food industry. Different approaches were used to enhance the viability of probiotics including microencapsulation and layer-by-layer cell coating. The of aim of this study was to evaluate the viability of coated Lacticaseibacillus rhamnosus using layer-by-layer (LbL) technique with black seed protein (BSP) extracted from Nigella sativa defatted seeds cakes (NsDSC), as a coating material, with alginate, inulin or glucomannan, separately, and the final number of coating layers was 3. The viable cell counts of the plain and coated L. rhamnosus were determined under sequential simulated gastric fluid (SGF) for 120 min and simulated intestinal fluid (SIF) for 180 min. Additionally, the viability after exposure to 37, 45 and 55°C for 30 min was also determined. Generally, the survivability of coated L. rhamnosus showed significant (p≤ 0.05) improvement (<4, 3 and 1.5 logs reduction for glucomannan, alginate and inulin respectively) compared with plain cells (~6.7 log reduction) under sequential exposure to SGF and SIF. Moreover, the cells coated with BSP and inulin showed the best protection for L. rhamnosus under high temperatures. Edible films prepared with pectin with LbL coated cells showed significantly higher values in their tensile strength (TS) 50% and elongation at the break (EB) 32.5% than pectin without LbL coated cells. LbL technique showed a significant protection of probiotic cells and potential use in food application.